Nutrition and Physical Activity Counseling by General Practitioners in China - Tan X; Xie H; Wang D (Dove Medical Press, 2023)
Xian Tan,1,2 Hebin Xie,3 Danling Wang1- 3 1Hengyang Medical School, University of South China, Hengyang, Hunan, People's Republic of China; 2Institute for Future Sciences, University of South China, Changsha, Hunan, People's Republic of China; 3The Affiliated Changsha Central Hospital, Hengyang Medical School, University of South China, Changsha, Hunan, People's Republic of ChinaCorrespondence: Danling Wang, Hengyang Medical School, University of South China, 28 West Changsheng Road, Hengyang, Hunan, 421001, People's Republic of China, Email danlingwang@usc.edu.cnIntroduction: To reduce unhealthy lifestyles in China, it is critical to implement effective strategies. Counseling provided by physicians is important for assisting patients in improving their lifestyles, and general practitioners (GPs) are the main providers of lifestyle counseling to patients. However, few studies have focused on the lifestyle counseling practices by GPs in China, particularly in regard to nutrition and physical activity.Objective: The aims of this study are: (i) to examine the current practice of Chinese GPs in counseling patients regarding nutrition and physical activity; (ii) to understand the common barriers to such counseling by Chinese GPs; and (iii) to study the association between GPs' personal lifestyle choices and their practices in lifestyle counseling.Methods: A cross-sectional, self-reported online questionnaire was conducted among GPs in Hunan province, China. A total of 198 GPs completed the questionnaire.Results: The majority of GPs provide nutrition and physical activity counseling to less than 40% of their patients, spending less than three minutes per counseling session. The main reported barriers to counseling on nutrition and physical activity are inadequate time and a lack of knowledge or experience. GPs primarily acquire knowledge through medical books and journals, followed by science popularization. Furthermore, GPs who maintain healthier lifestyle habits, possess a better understanding of lifestyle guidelines, conduct longer office visits, and exhibit higher self-efficacy are more likely to provide counseling to patients.Conclusion: This study highlights the need for improvement in nutrition and physical activity counseling among Chinese GPs. GPs' personal nutrition and physical activity habits may measurably influence their counseling practice. We recommend that GPs themselves adopt healthier lifestyle habits to potentially improve their counseling practice. Moreover, proactive measures should be taken to assist GPs in overcoming barriers encountered with lifestyle counseling.Keywords: nutrition counseling, physical activity counseling, lifestyle counseling, general practitioner, China